2015
DOI: 10.1002/adfm.201502153
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Lipid Bilayer Membranes for Enhanced Detection Sensitivity of Biolabeling Fluorophores

Abstract: Plasmonics based sensing using the surface plasmon resonance of metal nanoparticles has been effectively demonstrated in various applications. Extending this methodology to cell and artificial lipid bilayer membranes would be extremely beneficial in enhancing the sensitivity of the detection of binding and cellular transport of molecules across such membranes. Here we demonstrate the creation of a artificial plasmonic biomembrane template and use it to demonstrate the enhanced detection sensitivity of certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Recent advancements in nanoplasmonics and nanophotonics enable the enhancement of chiral fields near the absorption maxima of chiral molecules and are therefore useful for enhancing the CD spectrum. However, most of these structures are chiral themselves and the resulting enhanced molecular CD contains the effect of the chiral photonic structures as well. Recently, “super-chiral” fields, generated using plasmonic and photonic nanostructures, were shown to enhance dissymmetric CD signals more than circularly polarized light . However, these super chiral fields are not uniform over the volume of the nanostructures and this results in a great difficulty in deterministic placement of chiral molecules in the enantiopure super chiral hot spots or in large chiral molecule thin films …”
Section: Introductionsupporting
confidence: 91%
“…Recent advancements in nanoplasmonics and nanophotonics enable the enhancement of chiral fields near the absorption maxima of chiral molecules and are therefore useful for enhancing the CD spectrum. However, most of these structures are chiral themselves and the resulting enhanced molecular CD contains the effect of the chiral photonic structures as well. Recently, “super-chiral” fields, generated using plasmonic and photonic nanostructures, were shown to enhance dissymmetric CD signals more than circularly polarized light . However, these super chiral fields are not uniform over the volume of the nanostructures and this results in a great difficulty in deterministic placement of chiral molecules in the enantiopure super chiral hot spots or in large chiral molecule thin films …”
Section: Introductionsupporting
confidence: 91%
“…The design and fabrication of conductive nanostructures for plasmon-enhanced spectroscopy has become a field of intense research due to their application in molecular sensing and biosensing. [1][2][3][4][5] Under ideal conditions, extreme sensitivity can be reached, pushing the performances of optical measurements in terms of spatial resolution, [6][7] and sensitivity down to the single molecule level. [8][9][10] Metallic nanostructures with rational dimensions and shapes can, in ideal experimental conditions, locally enhance and confine an electromagnetic field that can be used as a local antenna either in collection (enhancement of the impinging light) or in emission (enhancement of the emitted field).…”
Section: Introductionmentioning
confidence: 99%
“…The design and fabrication of conductive nanostructures for plasmon-enhanced spectroscopy has become a field of intense research due to their application in molecular sensing and biosensing. Under ideal conditions, extreme sensitivity can be reached, pushing the performances of optical measurements in terms of spatial resolution, , and sensitivity down to the single molecule level. Metallic nanostructures with rational dimensions and shapes can, in ideal experimental conditions, locally enhance and confine an electromagnetic field that can be used as a local antenna either in collection (enhancement of the impinging light) or in emission (enhancement of the emitted field) . When a molecule of interest is placed in these nanoscale regions of electromagnetic enhancement, the magnitude of the enhanced vibrational spectra depends on numerous factors, including geometrical factors (i.e., the design of the structure with respect to an excitation wavelength and an input polarization), distribution, and density of the molecular species over the structure and of the considered optical process.…”
Section: Introductionmentioning
confidence: 99%
“…Model biological membranes have been widely used to understand the organizational and dynamical aspects of real cell membranes as well as their interactions with proteins, polymers and nanoparticles. [18][19][20][21][22][23][24][25][26][27][28] In this regard, several recent studies with supported lipid bilayer (SLB) membranes and LLO PFTs have revealed the subtle dependence of the nature of protein assemblies and pores formed on the composition of lipid membranes. 29,30 Obtaining microscopic insight into the causal connection between lipid composition and pore formation efficacy has proven to be difficult, largely due to both the small length scale involved for both pore formation (10-100 nm) as well as the dynamic and co-operative nature of the potential interaction and response.…”
Section: Introductionmentioning
confidence: 99%